COVID-19 lockdown policy and heterogeneous responses of urban mobility: Evidence from the Philippines - Yi Jiang; Jade R. Laranjo; Milan Thomas (Asian Development Bank (ADB), 2022)
Throughout 2020, national and subnational governments worldwide implemented nonpharmaceutical interventions (NPIs) to contain the spread of coronavirus disease (COVID-19). These included community quarantines, also known as lockdowns, of varying length, scope, and stringency that restricted mobility. To assess the effect of community quarantines on urban mobility in the Philippines, we analyze a new source of data: cellphone-based origin-destination flows made available by a major telecommunication company. First, we demonstrate the impulse responses of mobility to lockdowns of varying stringency levels over six months starting in March 2020. Then we assess the heterogeneous effects of lockdowns by city characteristics, focusing on employment composition. This analysis reveals that the effect of lockdowns was strongest in cities where a high share of workforce was employed in work-from-home-friendly sectors or medium to large enterprises. We compare our findings with cross-country evidence on lockdowns and mobility, discuss the economic implications for containment policies in the Philippines, and suggest additional research that can be based on this novel dataset.
Keywords: I18; J61; K32; O18; 330; mobility; employment; lockdowns; nonpharmaceutical interventions; remote work